MAPPING HISTORIC AND CURRENT DISTRIBUTION OF MARBLED TEAL (Marmaronetta angustirostris) IN PAKISTAN - H. Chaudhry; Z. Ahmad; H. Ali; M. Atiq-ur-Rahman; N. Nisar; A. Tahir (Journal of Animal and Plant Sciences, 2019)
There are deficiencies regarding status, distribution, seasonal movements and habitat use by birds, and this is particularly evident in case of wetland species. In order for developing action plans necessary to safeguard species threatened by human pressure, availability of data on distribution, breeding and population trends is imperative. Population of Marbled Teal has drastically reduced as a result of degradation, destruction and fragmentation of its habitat, worldwide. Marbled Teal population, therefore, qualifies vulnerable status in IUCN Red List. There is a dire need to develop a national conservation and management plan to protect Marbled Teal and its wetland habitat in Pakistan. In order for the conservation plans to be effective the spatial distribution of species in question needs to be accurately estimated. Only in this way the conservationists can assess the species distribution in response to climate change and anthropogenic alterations. The present study provides historic records and current distribution status of Marbled Teal in Pakistan. GIS mapping of distribution data gives added advantage and information necessary for planning conservation strategies for Marbled Teal. A careful scrutiny of the results revealed that Marbled Teal is a species of special concern as its habitat has undergone major devastations due to destruction and fragmentation. Comparisons made on the historic, fairly recent and recent distributions of Marbled Teal unfolded the fact that the species has a restricted geographical distribution which has become even more restricted in the recent times in Pakistan.
Keywords: Marbled Teal; GIS; conservation; wetlands; historic and current distribution data.